Maximizing reliability of distributed computing system with task allocation using simple genetic algorithm - Vidyarthi D.P.; Tripathi A.K. (My University, 2025)
Reliability is one of the very important characteristics of the distributed computing system (DCS), and articles on task allocation (an NP-Hard problem) to maximize the reliability of DCS have appeared in the past [S. Kartik, C.S. Ram Murthy, IEEE Trans. Comput. 46 (6) (1997) 719; S.M. Shatz, Wang, Goto, IEEE Trans. Comput. 41 (90) (1992) 1156]. Genetic Algorithm (GA) has emerged as a successful tool for optimization purposes. We, in this work, have used a simple GA to optimize the reliability of DCS with task allocation. © 2001 Elsevier Science B.V. All rights reserved.